Model-based cost optimization of a reaction–separation integrated process for the enzymatic production of the rare sugar d-psicose at elevated temperatures. (1st December 2015) - Wagner, N.; Bosshart, A.; Wahler, S.; Failmezger, J.; Panke, S.; Bechtold, M.
Abstract: The integration of biocatalysis with continuous separation of product and substrate constitutes an attractive option for overcoming the intrinsic yield limitation in enzymatic reactions that suffer from an unfavourable position of the equilibrium. One example is the recently established continuous process combining enzymatic epimerization in an enzyme membrane reactor ( EMR ), simulated moving bed ( SMB ) chromatography and nanofiltration for the high-yield production of the rare sugar d -psicose from its bulk epimer d -fructose with recycling of the unused epimer to the EMR . In this work, we present a first, comprehensive analysis of this novel reaction-separation process concept on the basis of an integrated process model. Therefore, a process model consisting of a continuous stirred tank reactor model with reversible Michaelis–Menten kinetics for representation of EMR operation, a transport-dispersive true moving bed model for representation of SMB operation and an ideal filtration model was constructed. As enzyme costs are particularly difficult to estimate due to their strong dependence on the reactor temperature, we further established a model-based procedure for characterizing the biocatalyst in terms of operational stability and activation as a function of the reactor operating temperature. The integrated process model then enabled the identification of optimum operating points for a fully integrated process operation. First, the established design procedure was used to implement a highly productive run on our existing lab-scale plant (i.e. 2.3 kg of d -psicose per L of SMB column volume and day and 4.5 kg d -psicose per g enzyme and day), where Dpsicose was produced both at high purity (≈ 98%) and at remarkable yield (96%). Next, the established process model was used for the optimization of the overall process economics. Therefore, a comprehensive analysis of the process in terms of suitable reactor temperatures was performed based on a multi-objective function addressing important cost contributions in the integrated process (i.e. enzyme, desorbent, solid phase, substrate). The presented integrated process scheme can be easily adapted to a number of similar isomerization and epimerization reactions enabling economic production of (almost) the complete set of C6 sugars. Highlights: Rational design of a novel biocatalysis-separation integrated process was presented. A highly productive experimental run was implemented on a lab-scale plant. The enzyme reactor temperature was addressed as key variable during optimization. Overall process economics were optimized using a cumulative cost function.